Efficiency of New Zealand's District Health Boards at Providing Hospital Services: a Stochastic Frontier Analysis - Jiang, N (Seoul National University, 2018)
The majority of secondary and tertiary healthcare services in New Zealand are provided through public hospitals managed by 20 local District Health Boards (DHBs). Their performance were measured by a set of indicators established by the National Heath Targets including elective surgeries, cancer treatment, and Emergency Department waiting times etc. Due to data issues and ill-judged generic public perceptions, efficiency studies for the NZ health system is insufficient in spite of its common international applications within the field of applied production economics. This inevitably leads to criticisms about the perverse incentives created by the Health Targets and its final abolishment by the newly elected Labour Government in January 2018. Utilizing a multifaceted administrative hospital dataset, this study is the first to measure both the technical and cost efficiency of NZ public hospitals during the period of 2011-2017. More specifically, it deals with the question of how hospital efficiency varies with activities reported under the National Health Targets after controlling for local patient structure. There is no evidence in the empirical results to suggest the proportions of elective surgical discharges or Emergency Department visits are increased at the expenses of lowering the overall efficiency of hospital operations. The national technical efficiency is averaged at 86 percent over the period and cost efficiency is 85 percent. The results are derived by stochastic input distance function and cost frontier in order to accommodate multiple outputs and limited number of census observations. Efficiency ranking is sensitive to specifications of the inefficiency error term, but reasonably robust to the choice of functional form and different proxies for capital input.